Особливості взаємозв’язків координаційних здібностей із психічними процесами та властивостями в молодших школярів із затримкою психічного розвитку - Тучак, Олег; Коць, Михайло; Tuchak, Oleh; Kots, Mykhaylo (Східноєвропейський національний університет імені Лесі Українки, 2015)
Затримка психічного розвитку в дітей молодшого шкільного віку – актуальна проблема сьогодення. Вона потребує нових підходів до корекції патологічних станів у процесі фізичного виховання. Mental development delay of children of junior school age is a topical problem nowadays. It requires new approaches in correction of pathological conditions in the process of physical education. It is proved the hypothesis about existence of interconnections of coordinating skills with psychological processes and characteristics. With the help of correlational analysis it was established the more complicated according to its structure coordinating quality the more number of coordinating skill and mental processes and qualities it correlates. The perspective of the study is development of methodology of studying of coordinating exercises by pupils of junior school age with mental development delay at lessons of physical culture. It is foreseen that development of coordinating skills will contribute to positive changes in mental processes and characteristics of junior pupils.
Coordinating Abilities with Psychological Processes and Characteristics of Junior Pupils with Mental Development Delay
Keywords: затримка психічного розвитку; кореляція; координація; учні молодшого шкільного віку; mental development delay; correlation; coordination; pupils of junior school age